Belize : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper provides an overview of Belize's tourism sector and main achievements and discusses the country's comparative advantages and bottlenecks in tourism. It also analyzes the impact of structural and institutional reforms on tourist arrivals. The outturns in tourism have significantly exceeded targets set in the authorities' National Sustainable Tourism Masterplan (NSTMP). The implementation of the NSTMP reforms has supported the tourism sector's expansion. In order to guide the development of the tourism sector, the NSTMP 2011 proposes reforms and targets to propel Belize into an internationally recognized tourist destination by 2030. The emergence of the shared economy business model has also brought new challenges, in addition to opportunities. The benefits of the peer-to-peer accommodation available to customers on digital platforms include the expansion of tourism product, service, and sector offerings; improved access to market; and opportunities for income generation. It is imperative that reforms in the near term should focus on addressing the impact of recurring natural hazards, infrastructure bottlenecks, fortifying the institutional and governance framework, reducing crime, and mitigating concerns relating to the shared economy.